ENHANCING NATION BUILDING: A STUDY OF COUNSELOR PERSPECTIVES ON BEHAVIORAL THERAPIES, CRIME PREVENTION AND SAFETY MANAGEMENT AMONG TERTIARY INSTITUTION STUDENTS IN TARABA STATE, NIGERIA (American Journal of Pedagogical and Educational Research, 2024)
This paper investigates the impact of behavioral approach on crime prevention and safety management among tertiary students in Taraba State, Nigeria. A descriptive and survey study approach was used to obtain data from 500 participants. Participants were drawn from six tertiary institutions, and their responses were analyzed to determine the efficacy of various behavioral therapies and their perceived importance in crime prevention and safety management. The findings revealed that the most frequently utilized behavioral therapies are positive reinforcement, motivational interviewing, and social skills training, with positive reinforcement being the most common. The study also finds that a sizable proportion of respondents consider the behavioral approach to be very important or extremely important in counseling. Furthermore, the importance of behavioral therapies in creating positive changes in students is demonstrated, with 72% of participants agreed to very effective or extremely effective. The ANOVA results show a statistically significant relationship between the perceived importance of the behavioural approach and its effectiveness in reducing crime rates, leading to the rejection of the null hypothesis. The regression analysis confirms a significant linear relationship between the importance level and the effectiveness of behavioural therapies. The study suggests that the behavioural therapies have a considerable impact on crime rates and Safety Management among tertiary institution students in Taraba State, with perceived relevance playing an important part in its efficacy for national development.